2020
DOI: 10.1186/s40991-020-00053-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementing part-time leadership as instrument for sustainable HR management

Abstract: This paper discusses the suitability of part-time leadership as instrument for a sustainable Human Resources Management (HRM) policy. The concept of part-time leadership is introduced and discussed based on a meta-analysis of existing studies and latest research that has been executed on‚ atypical‘working time arrangements in leadership positions. The article discusses the intersection of part-time leadership with the three subject areas (economic, social and ecological) of the Triple-Bottom Line and tries to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Going by the ideas of Karlshaus and Kaehler (2017d) in their studies it was evident that part-time employment (being a dimension of atypical employment relationship), in leadership sphere, largely address flexible work hours and hourly reductions for a superior harmonisation of work and family. Going by the tenets of sustainable human resource social framework, part-time employment thus improves social life of employees by virtue of its impact on the family life (Karlshaus, 2016)as it not only assist to reconcile the interests of the organization with those of the individual leader as an employee, but also with the higher interest of family members and society.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Going by the ideas of Karlshaus and Kaehler (2017d) in their studies it was evident that part-time employment (being a dimension of atypical employment relationship), in leadership sphere, largely address flexible work hours and hourly reductions for a superior harmonisation of work and family. Going by the tenets of sustainable human resource social framework, part-time employment thus improves social life of employees by virtue of its impact on the family life (Karlshaus, 2016)as it not only assist to reconcile the interests of the organization with those of the individual leader as an employee, but also with the higher interest of family members and society.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The findings revealed a positive and significant relationship between telecommuting and organizational performance of Mobile (GSM) telecommunication companies in Port Harcourt. Karlshaus (2016); Karlshaus, (2018); Karlshaus & Kaehler, (2017d) in their studies revealed that parttime leadership ideas and navigators largely address flexible work hours and hourly reductions for a superior harmonisation of work and family. Going by the tenets of sustainable human resource social framework, part-time employment thus improves social life of employee by virtue of its impact on the family life (Karlshaus, 2016) as it not only helps to reconcile the interests of the organization with those of the individual leader as an employee, but also with the higher interest of family members and society.…”
Section: Part Time Employment and Sustainable Humanmentioning
confidence: 99%
See 2 more Smart Citations